Electrically conductive polyetheretherketone nanocomposite filaments: from production to fused deposition modeling - Gonçalves, Jordana Catarina Carvalho (2018)
The present work reports the production and characterization of polyetheretherketone (PEEK) nanocomposite filaments incorporating carbon nanotubes (CNT) and graphite nanoplates (GnP), electrically conductive and suitable for fused deposition modeling (FDM) processing. The nanocomposites were manufactured by melt mixing and those presenting electrical conductivity near 10 S/m were selected for the production of filaments for FDM. The extruded filaments were characterized for mechanical and thermal conductivity, polymer crystallinity, thermal relaxation, nanoparticle dispersion, thermoelectric effect, and coefficient of friction. They presented electrical conductivity in the range of 1.5 to 13.1 S/m, as well as good mechanical performance and higher thermal conductivity compared to PEEK. The addition of GnP improved the composites’ melt processability, maintained the electrical conductivity at target level, and reduced the coefficient of friction by up to 60%. Finally, three-dimensional (3D) printed test specimens were produced, showing a Young’s modulus and ultimate tensile strength comparable to those of the filaments, but a lower strain at break and electrical conductivity. This was attributed to the presence of large voids in the part, revealing the need for 3D printing parameter optimization. Finally, filament production was up-scaled to kilogram scale maintaining the properties of the research-scale filaments.